1996
DOI: 10.1113/jphysiol.1996.sp021747
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ sparks involving multiple Ca2+ release sites along Z‐lines in rat heart cells.

Abstract: 1. High spatial resolution confocal imaging was used to investigate the fundamental nature of "Ca2+ sparks' in rat cardiac myocytes loaded with the fluorescent calcium indicator, fluo‐3. 2. The sites at which calcium sparks occurred (Ca2+ release sites) were packed closely and irregularly in transverse planes along Z‐lines (mean spacing between sites of 0.76 microns). In contrast, sites were spaced more regularly in the longitudinal direction, at intervals of 1.8 microns (i.e. the sarcomere length). 3. Diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
133
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(149 citation statements)
references
References 17 publications
11
133
5
Order By: Relevance
“…2C), whereas the rest is occupied by other organelles such as mitochondria (12). Because diffusion depends on the gradient and the projected area through which diffusion occurs (Fick's first law), our data can explain the unexpected observation that, in the rat, the apparent diffusion coefficient for Ca 2ϩ during a Ca 2ϩ spark is twice as large in the longitudinal direction compared with the transverse direction (19). For saltatory wave propagation between RyR clusters, the velocity should be proportional to D/d, where D is the apparent diffusion coefficient and d is a mean distance between release sites (20).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…2C), whereas the rest is occupied by other organelles such as mitochondria (12). Because diffusion depends on the gradient and the projected area through which diffusion occurs (Fick's first law), our data can explain the unexpected observation that, in the rat, the apparent diffusion coefficient for Ca 2ϩ during a Ca 2ϩ spark is twice as large in the longitudinal direction compared with the transverse direction (19). For saltatory wave propagation between RyR clusters, the velocity should be proportional to D/d, where D is the apparent diffusion coefficient and d is a mean distance between release sites (20).…”
Section: Discussionsupporting
confidence: 62%
“…For saltatory wave propagation between RyR clusters, the velocity should be proportional to D/d, where D is the apparent diffusion coefficient and d is a mean distance between release sites (20). From our measurements, the longitudinal spacing of release sites in the rat is Ϸ1.8 m, and the geometric mean transverse spacing is 0.8 m. From Ca 2ϩ spark properties, the apparent longitudinal and transverse diffusion coefficient are 7.9 and 17.1 m 2 /s, respectively (19). Therefore the ratio of transverse-to-longitudinal wave propagation velocity should be 7.9/0.8 to 17.1/1.8 (respectively) or 1.04, i.e., close to unity.…”
Section: Discussionmentioning
confidence: 96%
“…By showing the existence of events smaller than sparks, the present results indirectly suggest that sparks involve multiple channels in skeletal muscle. They also add, albeit indirectly, to the body of increasing evidence (Lipp & Niggli, 1996;Parker, Zang & Wier, 1996;Blatter, H user & R úos, 1997) that cardiac muscle sparks, which are larger and last longer than skeletal muscle sparks, also reflect activation of multiple release channels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have shown that localized and spontaneous intracellular calcium release events (i.e., calcium sparks) also arise from calcium release through ryanodine receptor channels in skeletal, cardiac, and smooth muscle cells (14)(15)(16)(17)(18)(19)(20). In porcine ASM cells, earlier studies revealed occurrence of calcium sparks that were grouped and coupled across adjacent regions of the cell (16).…”
Section: Spontaneous Calcium Release Events In Airway Smooth Muscle Cmentioning
confidence: 99%